Health Monitoring and Control of Civil Infrastructures using Wireless Smart Sensors - Abayomi Ajofoyinbo; David Olowokere (Bulletin of Electrical Engineering and Informatics, 2014)
This paper investigates health monitoring and control (HMC) of civil infrastructures using wireless smart sensor networks.  Two important requirements are (i) energy efficiency, and (ii) effective control to prevent damage of civil infrastructures.  Fuzzy control scheme is incorporated in the system model to provide capability for addressing problems of imprecision and uncertainty that can be associated with values of dynamic response.  Moreover, operation of wireless smart sensor networks is characterised as discounted semi-Markov decision process (SMDP) consisting of four states, namely: sleep, sense, store, and transmit.  The objective is to choose policy that offers optimal energy-efficient transmission of vibration-based dynamic response, and subsequently activate appropriate control.  Relevant mathematical representations are formulated for this model and its efficacy tested via numerical analysis,which is implemented in MATLAB software. It is shown by the results obtained that this HMC model can provide effective control and increase energy efficiency.